2018
DOI: 10.1038/s41570-018-0044-4
|View full text |Cite
|
Sign up to set email alerts
|

Methods for detection of cytosine and thymine modifications in DNA

Abstract: Methylation of cytosine at the 5-position is a common epigenetic marker in mammalian DNA, and plays an important role in regulating gene expression. Oxidised derivatives of 5-methylcytosine have recently been discovered. As well as being intermediates in an active demethylation pathway, some of these oxidised derivatives may function as epigenetic markers in their own right. Oxidised derivatives of thymine are also known as products of DNA damage. There is evidence however that one such derivative, 5-hydroxyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 212 publications
0
53
0
Order By: Relevance
“…Although the conductance distributions of the modified and canonical nucleotides still overlapped, the simulation study showed that the increased difference in molecular conductance was critical to efficient discrimination. Notably, the concept of chemistry‐assisted analysis of base modification in quantum‐tunneling‐based sensing would be further applicable to other modifications with available appropriate selective labeling reactions . Our work represents the first steps in the direct mapping of multiple species of modified nucleotides by means of quantum‐tunneling‐based single‐molecule sensing.…”
Section: Figurementioning
confidence: 94%
“…Although the conductance distributions of the modified and canonical nucleotides still overlapped, the simulation study showed that the increased difference in molecular conductance was critical to efficient discrimination. Notably, the concept of chemistry‐assisted analysis of base modification in quantum‐tunneling‐based sensing would be further applicable to other modifications with available appropriate selective labeling reactions . Our work represents the first steps in the direct mapping of multiple species of modified nucleotides by means of quantum‐tunneling‐based single‐molecule sensing.…”
Section: Figurementioning
confidence: 94%
“…Above the genetic code, there is a supra code called the epigenetic code, which is involved in cell differentiation, regulation of gene expression, development, and suppression of transposable elements (Bird, 2007;Berger et al, 2009). As one of the major epigenetic modifications, DNA methylation is a multifunctional marker that plays a direct role in the regulation of gene expression and an indirect structural role for the adjacent chromatin, as well as in the expression of miRNAs encoded in the genome (Berney and McGouran, 2018). From its side, miRNA is part of an active RNA-induced silencing complex (RISC) containing multiple associated proteins.…”
Section: Resolving Problems With Smart Base Substituentsmentioning
confidence: 99%
“…Nevertheless, these modifications are not directly detectable by most of the widespread sequencing or PCR-based methods, which makes some type of 5mC/5hmC-discriminating modification or enrichment a necessary step in the protocols. Chemical bisulfite conversion of unmethylated C to U underlies most PCR-based methods, methylation arrays, and sequencing approaches ( 82 ). Further development resulted in bisulfite-based oxBS-seq and TAB-seq protocols that differentiate between 5mC and 5hmC ( 83 , 84 ).…”
Section: Principles Of Detection and Challengesmentioning
confidence: 99%